Relationship between the fatigue behavior and grain structures of an as-extruded Mg-6.2%Zn-0.6%Zr (in wt.%) alloy. (20th June 2023) - Wang, B.J.; Xu, D.K.; Jiang, C.L.; Sheng, L.Y.; Han, E.H.
Highlights: The tension-tension fatigue behavior of an as-extruded ZK60 alloy is sensitive to the grain structure. The "bi-modal" grain structure has the lowest fatigue strength. Fatigue cracks in fine grain structure nucleate at the grain boundaries. Fatigue crack initiation of "bi-modal" and coarse grain structures is along slip bands. Abstract: Through investigating the tension-tension fatigue behavior of an as-extruded Mg-6.2 wt.%Zn-0.6 wt.%Zr (ZK60) alloy, it revealed that the determined fatigue strength at 10 7 cycles was quite sensitive to the grain structure. Among them, the fine grain structure had the highest fatigue strength of 130 MPa, whereas the typical "bi-modal" grain structure had the lowest fatigue strength of 110 MPa. Failure analysis demonstrated that for the fine grain structure, fatigue cracks preferentially nucleated at grain boundaries. For the "bi-modal" and coarse grain structures, the fatigue crack initiation was dominated by the cracking along slip bands. Graphical abstract: Image, graphical abstract